2003
DOI: 10.1097/01.ccm.0000063050.66813.39
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial hemodynamic and renal effects of intravenous enalaprilat following coronary artery bypass surgery complicated by left ventricular dysfunction*

Abstract: Intravenous enalaprilat safely and effectively improves cardiac and renal function following coronary artery bypass surgery complicated by postoperative left ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…They found that administration of intravenous ACE inhibitor improved the renal perfusion by counteracting the renin angiotensin system activity and that ACE inhibitors increased the cardiac output in patients with left ventricular dysfunction, thus, improving the renal perfusion. 3,16 The decrease in the rate of renal dysfunction that we observed in patients receiving preoperative ACE inhibitors may, therefore, be related to the protective effect of ACE inhibition on renal perfusion intra-operatively. Furthermore, preoperative ACE inhibitor therapy in the surgical population may be associated with a higher preoperative renal function reserve, making these patients less susceptible to renal injury during further CPB.…”
Section: Discussionmentioning
confidence: 99%
“…They found that administration of intravenous ACE inhibitor improved the renal perfusion by counteracting the renin angiotensin system activity and that ACE inhibitors increased the cardiac output in patients with left ventricular dysfunction, thus, improving the renal perfusion. 3,16 The decrease in the rate of renal dysfunction that we observed in patients receiving preoperative ACE inhibitors may, therefore, be related to the protective effect of ACE inhibition on renal perfusion intra-operatively. Furthermore, preoperative ACE inhibitor therapy in the surgical population may be associated with a higher preoperative renal function reserve, making these patients less susceptible to renal injury during further CPB.…”
Section: Discussionmentioning
confidence: 99%
“…35 however, at times dopamine can help to initiate diuresis when a loop diuretic alone is insufficient. although aCe-i/arB therapy should be avoided in most cases, the use of intravenous enalaprilat 36 has improved kidney performance in patients who have undergone coronary artery bypass complicated by left ventricular dysfunction. intravenous pentoxifylline in elderly patients showed a prophylactic beneficial effect on postoperative organ function, but more studies are needed to assess its efficacy; 37 moreover, this compound is not available in the united states.…”
Section: Prevention Of Post-cvs Akimentioning
confidence: 99%
“…This therapy also improved cardiac and stroke volume indexes and lowered pulmonary vascular resistance. 55 In observational studies, Benedetto et al 58 evaluated the effect of preoperative ACE inhibitors on acute kidney injury (AKI) in 536 patients undergoing CABG. They found that the incidence of acute kidney injury (AKI) was 6.4% in patients with ACE inhibitors but 12.2% in patients without ACE inhibitors (OR 0.48, 95% CI 0.23-0.77; Po0.04).…”
Section: )mentioning
confidence: 99%
“…Several small randomized clinical trials (n¼14-40) provide evidence that perioperative ACE inhibitor therapy improved renal blood flow and/or function in patients undergoing cardiac surgery. [55][56][57] In the postoperative intensive care unit, Wagner et al investigated the effects of enalaprilat on cardiac and renal function in patients (n¼40) with a left ventricular ejection fraction o35% following CABG. The results showed that intravenous enalaprilat increased creatinine clearance and decreased serum creatinine and urea.…”
Section: )mentioning
confidence: 99%